Large-Group One-Session Treatment: Feasibility in Highly Height Fearful Individuals and Predictors of Outcome - Wannemueller, André; Gruszka, Piotr; Chwalek, Sarah; Fröhlich, Sonja; Mulders, Miriam; Schaumburg, Svenja; Schöttes, Johanna; Wiederhold, Sonja; Margraf, Jürgen (Frontiers in Psychology, 2019)
Objective: Exposure based large-group one-session treatments (LG-OSTs) proved feasible in different situational fears and showed promising short- and long-term outcomes. Based on prior LG-OST protocols we explored feasibility and effectiveness of an LG-OST protocol in four cohorts of highly height fearful individuals (N = 104). Moreover, we aimed to identify predictors of LG-OST in order to provide individualized treatment recommendations in the future. Method: Participants’ height fear was assessed at pre- and post-treatment as well as at five months follow-up using questionnaires and a behavioral approach test (BAT). Pre-treatment indices of negative emotional traits and positive mental health, the extent by which fear-evoking expectancies were violated during exposure, and post-treatment group perception processes were assessed in order to predict the outcome. Results: The LG-OST procedure proved feasible and effective in terms of both subjective and behavioral height fear. Post-treatment effects sizes of height fear questionnaires ranged between d = 0.94 – 1.43. After the treatment, about half of the participants (49.5%) were able to ascend an aerial fire ladder up to a maximum of 30 meters (vs. pre-treatment 17.3%). Follow up results showed the long-term stability of effects. Among psychological constructs, positive mental health and expectancy violation were the strongest predictors of LG-OST long-term outcome. Conclusions: We conclude that exposure based LG-OST are feasible, effective and very efficient compared to individual face-to-face settings. Thus, they represent very promising treatment alternatives for situational fears including height-fear. Moreover, clinical research may benefit from LG-OST protocols as its high standardization may facilitate the search for mediators and moderators of exposure outcomes.